ChemInform Abstract: Construction of Turmerone Motif‐Fused Spiropyrrolidine Oxindoles and Their Biological Evaluation for Anticancer Activities. Issue 29 (29th June 2016) - Liu, Xiong‐Li; Yang, Chao; Zhang, Wen‐Hui; Zhou, Gen; Ma, Xi‐Tao; Lin, Bing; Zhang, Min; Zhou, Ying; Feng, Ting‐Ting
Abstract: Facile and efficient methodology for the synthesis of novel turmerone motif‐fused spiropyrrolidine oxindoles via a multicomponent 1, 3‐dipolar cycloaddition reaction of dienones with azomethine ylides is reported.